Spatial variability of some physical properties of three soils at two depths - Machado, Rodrigo Vilella; Becegato, Valter Antonio; Rafaelli Neto, Sílvio Luís; Figueiredo, Olívia Aparecida Rodolfo (Revista de Ciências Agroveterinárias, 2006)
This work was carried out aiming to evaluate soil parameters such as bulk density, particle density and porosity through classical statistics and geostatistics techniques. Three soils were evaluated: Red-Yellow Latosol, Low Humic Gley soil and Bog soil. Samples were collected at 0 - 20 and 20 - 40 cm depth in a square grid with space varying from 0.75 to 4.5 m, resulting in twenty five points per layer. The Red- Yellow and on Low Humic Gley soil data analyses allowed the identification of a sampling space interval ranging from 1.5 to 5 m, establishing a limit where samples start being independent. Conversely, at the Bog soil, the sampling interval was larger than the sampling field dimension, precluding the identification of a similar limit.